Analisis Bisnis Model Free Mobile App pada Aplikasi Muslim Pro dalam Perspektif Islam - Fadillah, Hafizh (Educationist: Journal of Educational and Cultural Studies, 2023)
Social media is currently one of the impacts of technological developments that are popular with people around the world. Social media itself makes it easy to disseminate information in various fields, one of which is in business. Najla Farid utilizes social media as a medium for doing business, namely efforts to disseminate information, promote and sell her products widely to all groups, named Bittersweet by Najla. One of the efforts made is to create a marketing strategy on social media by hooking up celebrities who go viral easily to attract buyers. The purpose of this research is to analyze content marketing on social media Instagram Bitter Sweet by Najla.